Exploring agricultural levers for mitigating the overnutrition burden in India - Sachdev, H.P.S. (International Food Policy Research Institute, 2012)
The current concern n for and policy response to malnutrition in India is solely restricted to undernutrition diagnosed on the basis of body size (anthropometry). However, recent evidence indicates that the burden of overnutrition and related morbidities is rapidly escalating to alarming proportions. This research first examines the need to address overnutrition in India and subsequently explores the potential of the agricultural sector to mitigate the burden of over nutrition and related non-communicable diseases. The demographic, economic, and dietary transitions seen in India are causing rapid escalation in overnutrition and related morbidities, particularly in urban areas and higher-income groups but also among the poor, with faster escalation expected to occur among this group in the future